Development of Learning Media for Ubrug Traditional Theater Documentary Films for Class X Students at Senior High School 8 Serang City - Dimyati, Ahmad; Roekmana, Giri Mustika; Septiyan, Dadang Dwi (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2023)
This study aims to find out how the development and feasibility of Ubrug Traditional Theater Documentary Film learning media is motivated by the problems found at Senior High School 8 Kota Serang. This study uses research and development (R&D) research methods with the ADDIE research model which has five stages, namely analyze, design, development, implementation, and evaluation. Data collection techniques used were observation, interviews, and questionnaires. The data analysis technique uses descriptive quantitative analysis techniques. The results of this study indicate that the learning media for Ubrug Traditional Theater Documentary Film "Very Eligible" is used in a lesson. This is evidenced by the results of the material eligibility of 87% which is included in the "Very Eligible" category, the percentage of media eligibility is 96,3% which is included in the "Very Eligible" category, and the percentage of user responses is 81,5% which is included into the "Very Eligible" category, so it can be concluded that the Ubrug Traditional Theater Documentary Film media is very appropriate for use in learning.